Taragak Pulang Song: A Translation Studies of Minangkabau-English - Muhamad Saiful Mukminin; Libra Dui Putra (J-Lalite: Journal of English Studies, 2025)
The present research aims to analyse the translation techniques, methods, and underlying ideologies used in translating the Minangkabau song Taragak Pulang into English. The research adopts a qualitative descriptive approach grounded in translation theory. The data consists of the lyrics of Taragak Pulang in Minangkabau and their English translation. Data collection was conducted through direct observation and note-taking, focusing on key aspects of the song and its translation. Data analysis follows an interactive model, which includes data reduction, data presentation, and conclusion drawing/verification. The results show that the translation of this song employs various translation techniques, including established equivalence, adaptation, modulation, reduction, generalisation, amplification, particularisation, and transposition. The established equivalence technique is the most dominantly applied technique to ensure clarity of the song’s lyrics in the target language. In this case, the translation method is oriented toward the target language, utilising eight translation techniques. From the perspective of translation ideology, the analysis suggests that the translation of this song tends toward domestication, which involves adapting the source text to make it more suitable within the cultural and linguistic context of the target language.